Sistem Pengatur Running Text Menggunakan Bluetooth Dengan Interface Android Berbasis Arduino - Wijaya; Asni Tafrikhatin; Witadi, Rahmat; Jati Sumarah (JASATEC : Journal Students Of Automotive, Electronic and Computer, 2023)
Running text, commonly known as scrolling text, is a prevalent method of conveying information in public places such as places of worship, shopping centers, and stores. Despite its informative nature, updating running text is often hindered when users are not near a computer. This research employs the Research & Development methodology. The process involves stages of potential and problem identification, information collection, design conceptualization, development, testing, and product revision. The device utilizes Arduino Uno, DMD P10, and HC-05. Testing was conducted with character variations ranging from 23 to 64 within a distance of 20 meters. The results indicate a delay time of approximately 0.64 to 2.19 seconds. This demonstrates a solution that enables running text updates via Bluetooth connection from Android devices, helping to overcome the challenge of updates that are difficult without a PC/laptop.